Performance study of antenna sidelobe canceler - Плющ, Олександр Григорович (Science-based technologies, 2020)
In this paper transient performance of antenna sidelobe canceler is studied. As literature analysis indicates, it is not paid enough attention to research into the influence of different eigenvalues and corresponding eigenvectors of auxiliary antenna channels correlation matrix on the adaptation process. Additionally, the problems linked to the adaptation in abruptly changing interference situations are not fully explored. Hence, the impact of the correlation matrix eigenvectors corresponding to both distinct eigenvalues and singular eigenvalues is analyzed. It is established that if the initial value of the weight vector equals zero, weight vector trajectory always belongs to the subspace created by the eigenvectors corresponding to distinct eigenvalues and, in this case, good transient performance is secured. Computer simulation is carried out to study the processes. It helped to show that if the initial weight vector is shifted artificially into the subspace created by the eigenvectors corresponding to the singular eigenvalues, transient performance greatly degrades. It is shown that the situation when initial weight vector finds itself in the subspace created by the eigenvectors corresponding to the singular eigenvalues can occur naturally. For example, it can take place when, after the termination of the transient process, one of the interfering signals gets switched off. One of such situations is studied and it shows that adaptation process can greatly decelerate. To resolve the problem, it is proposed to obligatory set to zero the weight vector value. Computer simulation has shown that the gain from this approach can reach up to 4-5 dB. It is proposed to use obligatory setting to zero procedure in abrupt changes of the interference environment to improve transient performance in antenna sidelobe cancelers that are used in radiolocation and telecommunication networks.